Association of sunitinib concentration and clinical outcome in patients with metastatic renal cell carcinoma treated with a 2‐week‐on and 1‐week‐off schedule. (20th October 2021) - Ito, Takahiro; Yamamoto, Kazuhiro; Furukawa, Junya; Harada, Kenichi; Fujisawa, Masato; Omura, Tomohiro; Yano, Ikuko
Abstract: What is known and objective: Sunitinib is used as a first‐line therapy for metastatic renal cell carcinoma. The primary aim of this study was to determine the optimal total sunitinib (sunitinib plus N ‐desethyl sunitinib) trough concentration for the alternative dosing schedule: 2‐week‐on and 1‐week‐off schedule (2/1 schedule). Methods: Patients with metastatic renal cell carcinoma treated with the 2/1 schedule of sunitinib, whose total sunitinib concentrations were available, were recruited for this study. Out of 19 patients, 17 whose sunitinib dosage was not changed until the measurement of drug concentration were eligible for the analysis of the relationship between total sunitinib concentration and clinical outcome. Individual pharmacokinetic parameters in 19 patients were estimated via the Bayesian analysis. Results: The onset of severe (grade ≥3) adverse effects among 17 patients during 3 weeks as a first course of sunitinib therapy was observed in 7 (41.2%) patients. The median total sunitinib concentration in patients with severe adverse effects was significantly higher compared with that in patients without severe adverse effects [median: 119 (113–131) vs . 87.8 (77.4–102) ng/mL, p = 0.01]. According to the receiver operating characteristic analysis of the onset of severe adverse effects, the cut‐off value of the total sunitinib concentration was 108 ng/mL. Patients with a total sunitinib concentration lower than 108 ng/mL had a longer time to first dose reduction or withdrawal due to adverse effects compared with those with a total sunitinib concentration of 108 ng/mL or higher ( p = 0.03). The probability without treatment failure was not significantly different between the two concentration groups. In addition, the estimated sunitinib apparent oral clearance (CL/F) was significantly lower in the severe adverse effects group. Our simulation demonstrated that 0.67‐time dose is needed for patients with approximately 90.0 ng/mL of sunitinib concentration on day 7 to maintain the concentration at the same level as the patients with higher CL/F. What is new and conclusion: Maintaining the total sunitinib trough concentrations of less than 108 ng/mL is safe to avoid the onset of serious adverse effects without increasing the treatment failure in patients with metastatic renal cell carcinoma treated with the 2/1 schedule of sunitinib. Abstract : Maintaining the total sunitinib trough concentrations of less than 108 ng/mL is safe to avoid the onset of serious adverse effects without increasing the treatment failure in patients with metastatic renal cell carcinoma treated with the 2/1 schedule of sunitinib.